2017
DOI: 10.18203/2320-1770.ijrcog20174022
|View full text |Cite
|
Sign up to set email alerts
|

Cellphone and media usage among adolescent girls of Bhopal city, Madhya Pradesh, India

Abstract: Background: Several researchers have reported that mobile phone uses are increasing among adolescents. Better understanding of cellphone and media usage by adolescents would help health care providers in guiding more responsible use of cellphone by teenagers. Aim of the study was to study the level and pattern of mobile phone usages among adolescent girls of Bhopal city, Madhya Pradesh.Methods: This cross-sectional study was conducted among adolescent girls between 14 to 19 years of age studying in schools of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The data from the final 11 studies only fit in to three main mHealth applications defined in the Out of eleven studies which were included, five were observational studies [21,23,25,29,30], one was cluster RCT [28], three were mixed-methods study [24,26,27] and remaining two were qualitative studies [20,22]. All these studies included in the review were published within the time period from 2009 to 2017.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data from the final 11 studies only fit in to three main mHealth applications defined in the Out of eleven studies which were included, five were observational studies [21,23,25,29,30], one was cluster RCT [28], three were mixed-methods study [24,26,27] and remaining two were qualitative studies [20,22]. All these studies included in the review were published within the time period from 2009 to 2017.…”
Section: Resultsmentioning
confidence: 99%
“…In India, a cross-sectional survey was conducted to study the level and pattern of mobile phone usage among adolescent girls. The study reported that most adolescent girls spent 2-4 hours a day on an average using smartphones and 69% adolescents preferred SMS for awareness about reproductive and sexual health information [30]. months that were sustained after 15 months for both 1-way and 2-way programs.…”
Section: Client Education and Behavior Change Communicationmentioning
confidence: 97%
See 3 more Smart Citations